Globaledge resource desk. (Lansing, MI : Michigan State University)
'Created by the Center for International Business Education and Research at Michigan State University (MSU-CIBER), globalEDGE is a knowledge web-portal that connects international business professionals worldwide to a wealth of information, insights, and learning resources on global business activities. Partially funded by a U.S. Department of Education Title VI B grant, globalEDGE is your source for global business knowledge.'
Keywords: Business enterprises -- Directories; International business enterprises -- Directories